Pemberdayaan UMKM Pedagang Sate Ayam di Mall Taman Anggrek melalui Program Pembinaan Terstruktur - Benny Cuaca; Bambang Widjanarko Susilo; Edy Susanto; Ayu Miranti Kusumaningrum; Galuh Aninditiyah; Rezky Eko Prasetyo; Zahra Dinul Khaq; Vivi Kumalasari Subroto; Febryantahanuji Febryantahanuji (Harmoni Sosial : Jurnal Pengabdian dan Solidaritas Masyarakat, 2025)
This community service activity aimed to provide guidance and capacity building for micro, small, and medium enterprises (MSMEs), specifically chicken satay vendors operating in the parking area of Taman Anggrek Mall, Jakarta. These culinary MSMEs have strong potential due to their strategic location, which attracts high foot traffic. However, many of these business owners still face challenges in managing and developing their businesses, particularly in terms of managerial skills, financial record-keeping, and marketing strategies. Therefore, this program was designed to enhance their business competitiveness by improving their managerial abilities, introducing simple bookkeeping practices, and promoting the use of digital platforms for marketing. The implementation of the program began with an initial observation to identify the specific needs and challenges faced by the MSME actors. This was followed by interactive training sessions covering topics such as the importance of basic financial management, how to create simple financial reports, and effective yet low-cost digital marketing strategies. In addition to the training, the team also provided intensive one-on-one mentoring to ensure that participants could apply the materials in their daily business operations. The outcomes of the program showed positive developments. The MSME participants began to recognize the importance of keeping financial records as a basis for making business decisions. They were also able to identify internal management issues such as inventory control and business planning. In terms of marketing, most of the vendors have started using digital platforms like WhatsApp Business and Instagram to promote their products, allowing them to reach a wider audience.It is expected that this community engagement initiative will continue and serve as a model for similar training programs targeting culinary MSMEs in other busy urban areas. Such efforts are essential to developing more independent, professional, and competitive MSMEs in the digital era.